2016
DOI: 10.1080/15592324.2016.1156833
|View full text |Cite
|
Sign up to set email alerts
|

How microRNA172 affects fruit growth in different species is dependent on fruit type

Abstract: microRNA172 (miR172) expression has been shown to have a positive effect on Arabidopsis fruit (siliques) growth. In contrast, over-expression of miR172 has a negative influence on fruit growth in apple, resulting in a dramatic reduction in fruit size. This negative influence is supported by the results of analyzing a transposable element (TE) insertional allele of a MIR172 gene that has reduced expression of the miRNA and is associated with an increase in fruit size. Arabidopsis siliques are a dry fruit derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 20 publications
1
24
1
Order By: Relevance
“…Its target gene AP2 is a negative regulator of fruit ripening with evidence that knock-down of SlAP2a leads to orange color, split open and bumpy surface of fruits in tomato 80 . Moreover, recent studies found that the miR172- AP2 pathway affects fruit size in different species depending on fruit type 57 (Fig. 5a ).…”
Section: Small Rna Research In Horticultural Plantsmentioning
confidence: 87%
“…Its target gene AP2 is a negative regulator of fruit ripening with evidence that knock-down of SlAP2a leads to orange color, split open and bumpy surface of fruits in tomato 80 . Moreover, recent studies found that the miR172- AP2 pathway affects fruit size in different species depending on fruit type 57 (Fig. 5a ).…”
Section: Small Rna Research In Horticultural Plantsmentioning
confidence: 87%
“…Additionally, the miR-139 in bovine MDSCs and C2C12 cells had different target genes which had different seed sites of their miRNAs. Yao, Tomes, Xu, and Gleave (2016) reported that miR-172 has different effects on the development and growth of Arabidopsis and apple and tomato fruits, thus suggesting that the same miRNA can perform different functions in different species. SP1, BMP4, HMGA1-Id3, and MYF6 are proteins closely related to cell proliferation or differentiation (Brocher, Vogel, & Hock, 2010;Guo, Degnin, Fiddler, Stauffer, & Thayer, 2003;Ju, Yang, Sheng, & Qi, 2016) that also represent targets of miRNA regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The AP2 family belongs to class A genes of floral organ identities. Transgenic plants expressing A. thaliana wild type AP2 and miR172 resistant AP2 genes did not show any phenotype due to regulation by the endogenous miR172, rather the overexpression of a miR172-resistant form of AP2 cDNA showed floral patterning defects, indicating the loss of floral organ determinancy [79]. Other AP2-like genes, such as Target of Eat1 (TOE1), TOE2 and TOE3 in A. Thaliana, or Indeterminate Spikelet1 and Gloy15 in Z. Mays, are also under the regulation of miR172.…”
Section: Flowering Time Regulation and Organ Developmentmentioning
confidence: 95%